Is Hedysarum mackenzei (Wild Sweet Pea) Actually Toxic? - Treadwell, Edward M; Clausen, Thomas Paul (Ethnobotany Research and Applications, 2008)
Hedysarum mackenzii (wild sweet pea, bear root) is widely regarded as toxic and warnings about confusing it with its edible cousin H. alpinum (Eskimo potato) abound. To find the chemical basis for this claim, we performed an exhaustive comparison of the secondary chemistry between the two plants as well as a search for nitrogen containing metabolites (alkaloids) in both species. No chemical basis for toxicity could be found. These results were consistent with a subsequent cytotoxic assay performed on an extract of H. mackenzii. Finally, a critical examination of the literature could find no credible evidence that H. mackenzii is toxic in spite of these widespread rumors.